2000
DOI: 10.1016/s0928-8244(00)00199-1
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody response during sepsis against targets expressed by methicillin resistant Staphylococcus aureus

Abstract: The identification of target structures is a prerequisite for the development of new treatment options, like antibody based therapy, against methicillin resistant Staphylococcus aureus (MRSA). In this study we identified immunodominant structures which were expressed in vivo during sepsis caused by MRSA. Using human sera we compared the immune response of humans with MRSA sepsis with the immune response of normal individuals and asymptomatically colonized individuals. We identified and characterized four staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 21 publications
3
48
0
Order By: Relevance
“…SERP0318 is also similar to S. aureus Sle1 (46% identical), which is an autolysin with Nacetylmuramyl-L-alanine amidase activity (27). SERP2263 also appears to contain an N-acetylmuramoyl-L-alanine amidase as well as a transglycosylase domain, while IsaA is annotated as a transglycosylase, and both are known virulence factors (35,56). Secreted proteases play an important role in virulence by scavenging nutrients in the form of short peptides, processing other extracellular bacterial proteins, and degrading host proteins.…”
Section: Discussionmentioning
confidence: 90%
“…SERP0318 is also similar to S. aureus Sle1 (46% identical), which is an autolysin with Nacetylmuramyl-L-alanine amidase activity (27). SERP2263 also appears to contain an N-acetylmuramoyl-L-alanine amidase as well as a transglycosylase domain, while IsaA is annotated as a transglycosylase, and both are known virulence factors (35,56). Secreted proteases play an important role in virulence by scavenging nutrients in the form of short peptides, processing other extracellular bacterial proteins, and degrading host proteins.…”
Section: Discussionmentioning
confidence: 90%
“…We have also shown that another important antigenic protein, IsaA (immunodominant staphylococcal antigen), is probably regulated by the YycG/YycF system as well. Although the putative function of this protein is still unknown, the high rate of antibodies raised against IsaA and found during sepsis caused by methicillin-resistant S. aureus shows that this protein is expressed at a high rate during infection, which could suggest a putative role in colonizing host tissues (25). Although it has to be verified, three other genes encoding potential virulence factors implicated in interactions with the host extracellular matrix may also be regulated by YycG/YycF.…”
Section: See Materials and Methods) His-tagged Yycf Andmentioning
confidence: 99%
“…An inspection of the genome sequence in the vicinity of arcC reveals the presence of a putative virulence factor, clumping factor B (clfB), approximately 1 kb downstream of arcC, and two further putative virulence factors, aureolysin (aur) (29) and isaB, approximately 6 kb upstream of this locus. clfB is known to be associated with the cell wall (25,26), and isaB is known to elicit an immune response (18); both of these genes probably encode proteins that are exposed to the host immune response and hence are likely to be subject to diversifying selection. Recombinational replacements within these genes, selected as they introduce genetic diversity, will frequently extend into flanking genes and may influence the sequence evolution of arcC.…”
Section: Delineation Of Clonal Groups and A Comparison Of Isolates Frmentioning
confidence: 99%